Promoting medical tourism: a multimodal communicative framework in private hospitals from an intercultural perspective - Wan Fatimah Solihah Wan Abdul Halim; Intan Safinaz Zainudin; Nor Fariza Mohd Nor; Badriyah Yusof (Penerbit Universiti Kebangsaan Malaysia, 2024)
The medical tourism industry, seriously affected by the coronavirus disease of 2019 (COVID-19), must effectively communicate its online promotional messages to boost the sector. Given that the medical tourism sector is a global one, cultural diversity is also essential. Studies on cultural heterogeneity, however, have only looked at one type of discourse, primarily the linguistic mode. Previous research failed to consider the multimodal approach, which could have hindered anticipated promotional messages from reaching potential foreign medical tourists. This study examines how 12 hospital web pages from Malaysia and Singapore combine several modes to provide marketing messages to foreign medical tourists. From a Systemic Functional Linguistic (SFL) standpoint, linguistic analysis was conducted using Halliday and Matthiessen’s (2004) model of metafunction theory, while visual analysis was conducted using Kress and van Leeuwen’s (2006) framework. The multimodal data were further analyzed using Hall’s cultural dimension of context-dependency, which classifies cultures into high-context and low-context cultures. The selected Malaysian and Singaporean hospital web pages primarily exhibit characteristics commonly found in low-context cultures, including detailed code systems, clear and explicit messages, highly structured content, information focus, and linear organization. These findings were inconsistent with the existing intercultural communication literature, which typically associates Asian countries with high-context cultures. The study’s contribution in the form of a multimodal communicative framework aims to help stakeholders and copywriters in medical tourism understand potential cultural sensitivity and communicative strategies while designing successful medical tourism websites for international promotion. It is crucial for medical tourism websites to effectively deliver promotional messages to prospective medical tourists during this COVID-19 recovery phase as it can be one of the ways to establish trust and reliance.